Person, Relationship and Love: The Contribution of a Personalist Pedagogical Anthropology for Promoting Educational and Helping Relationships - Musaio, Marisa (Paedagogia Christiana, 2025)
By considering the perspective of dialogue between pedagogy and personalism (Vico, 2002; Mari, 2006; Musaio, 2009), the contribution presents a pedagogical anthropology for educational and helping professions that highlights the significance of the connection between person and relationship. When educators and professionals face challenges, discomfort, and wounded existences, they rely on various ‘forms of life’ (Zambrano, 1996) and employ a sensitive reason to uncover the implicit, unspoken, and profound dimensions of every person and their educational and helping relationships. By actively participating in a helping relationship, they contribute to delineating a ‘loving educational action’ as a fundamentally essential approach, as a way of experiencing the encounter assuming responsibility for a helping relationship with the other, assisting them in uncovering and creating an order of the heart (De Monticelli, 2012), despite the difficulties endured.